2016
DOI: 10.1186/s40510-016-0140-2
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness comparison of mushroom and straight SS and TMA lingual archwires

Abstract: BackgroundThe aim of this study is to investigate the relative stiffness of straight and mushroom lingual archwires of different diameters, cross sections and alloys, plotting their load/deflection graphs and using a modified three-point bending test.MethodsFujita’s mushroom archwires and straight lingual archwires of different diameters, cross sections and alloys were derived by a virtual set-up of an equal malocclusion and were cut at their straight distal portion. These distal portions were tested using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Therefore, authors who compared in vitro the two types of mushroom and straight archwire observed that the advantages and disadvantages of some orthodontic movements varied for each archwire according to the treatment phase. 19,20 We believe that more studies on archwire shape should be performed (in vitro and in vivo) because it is still not possible to state which archwire shapes -mushroom, straight wire, Christmas tree or anatomical (the forms found in this study)-will be more suitable for treatment with the lingual technique. Therefore, the professional will have the opportunity to choose the shape of the archwire that better suits according to the clinical case being treated and, if possible, a template to assist in the orthodontic treatment.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, authors who compared in vitro the two types of mushroom and straight archwire observed that the advantages and disadvantages of some orthodontic movements varied for each archwire according to the treatment phase. 19,20 We believe that more studies on archwire shape should be performed (in vitro and in vivo) because it is still not possible to state which archwire shapes -mushroom, straight wire, Christmas tree or anatomical (the forms found in this study)-will be more suitable for treatment with the lingual technique. Therefore, the professional will have the opportunity to choose the shape of the archwire that better suits according to the clinical case being treated and, if possible, a template to assist in the orthodontic treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, authors who compared in vitro the two types of mushroom and straight archwire observed that the advantages and disadvantages of some orthodontic movements varied for each archwire according to the treatment phase. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Prior research has also demonstrated significant differences in the biomechanical systems of straight and mushroom lingual archwires. 7,8 Dental arch expansion through an engaged archwire is one of the strategies used in orthodontics to resolve dental crowding. Grauer and Proffit 9 demonstrated that fully customized lingual orthodontic appliances were accurate in achieving the goals planned in the initial set-up with the exception of the full amount of planned expansion.…”
Section: Introductionmentioning
confidence: 99%